(3cJGH GdhUjIs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3SHMGf GdChd bHd cd TF hGdGNQ HYO cd TF GYdece CNhGfi ef GdeDefjf Gfi YgOJ ai cJGHi gPG YgOi hTQMJ ajg Yde HdG QeR s
(3BNQgG (B:s
(3hbO LYdfc HgPG GdcJGH cCMOfG ai GdMceI hfXjQ dfG hdef JbOefG ai GdadGSaI GdPjf hgH Gddg dge QVhGfg JeJ GdQSGdI GdehSheI HGdhUjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs